Zachowanie się gruntów spoistych w warunkach powodzi i suszy = The behawior of cohesive soils in the flood and druaght condition - Grabowska-Olszewska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of physical property tests expressing hydrophilic properties of a mixture of the model clays (kaolinite and montmorillonite). It is shown that these properties are influenced by exchangeable cations (Ca. Na). The Casagrande method for determination of the liquid limit produces higher values than those obtained using the cone method. The chemical composition of water is responsible for physical and mechanical properties.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)